Waste Input-Output Analysis Concepts and Application to Industrial Ecology - Nakamura, Shinichiro; Kondo, Yasushi (Eco-Efficiency in Industry and Science, 2009)
The increasing use of input-output analysis (IOA) in Industrial Ecology (IE) for life-cycle assessment (LCA), material flow analysis (MFA), and life-cycle costing (LCC) calls for a self-contained publication on IOA that can meet the needs of practitioners without compromising on basic concepts and latest developments. "Waste Input-Output Analysis" addresses these needs. The standard IOA has the weakness that it does not consider the physical flows of waste and the activity of waste management. To cope with this problem, the authors have developed the Waste Input-Output model (WIO) which addresses these issues explicitly. The major aim of this book is to make WIO accessible to the students and practitioners of IE. "Waste Input-Output Analysis" is unique in its coverage of both the basics of IOA and its application to IE with special emphasis on issues of waste management. No pre-knowledge is required on IOA.